Weather radar data correlate to hail‐induced mortality in grassland birds. Issue 2 (24th March 2017) - Carver, Amber R.; Ross, Jeremy D.; Augustine, David J.; Skagen, Susan K.; Dwyer, Angela M.; Tomback, Diana F.; Wunder, Michael B.
Abstract: Small‐bodied terrestrial animals such as songbirds (Order Passeriformes) are especially vulnerable to hail‐induced mortality; yet, hail events are challenging to predict, and they often occur in locations where populations are not being studied. Focusing on nesting grassland songbirds, we demonstrate a novel approach to estimate hail‐induced mortality. We quantify the relationship between the probability of nests destroyed by hail and measured Level‐III Next Generation Radar (NEXRAD) data, including atmospheric base reflectivity, maximum estimated size of hail and maximum estimated azimuthal wind shear. On 22 June 2014, a hailstorm in northern Colorado destroyed 102 out of 203 known nests within our research site. Lark bunting ( Calamospiza melanocorys ) nests comprised most of the sample ( n  =   186). Destroyed nests were more likely to be found in areas of higher storm intensity, and distributions of NEXRAD variables differed between failed and surviving nests. For 133 ground nests where nest‐site vegetation was measured, we examined the ameliorative influence of woody vegetation, nest cover and vegetation density by comparing results for 13 different logistic regression models incorporating the independent and additive effects of weather and vegetation variables. The most parsimonious model used only the interactive effect of hail size and wind shear to predict the probability of nest survival, and the data provided no support for any of the models without this predictor. We conclude that vegetation structure may not mitigate mortality from severe hailstorms and that weather radar products can be used remotely to estimate potential for hail mortality of nesting grassland birds. These insights will improve the efficacy of grassland bird population models under predicted climate change scenarios. Abstract : The contribution of hail to wildlife mortality is understudied, because hail storms are difficult to predict and collecting post‐storm mortality data require knowing where the greatest impact has occurred. Our study demonstrates that Level‐III NEXRAD data were strongly correlated with the distribution of hail‐induced nest mortality for ground‐nesting songbirds (Order Passeriformes) during a severe hail storm on 22 June 2014. We found that vegetation did not reduce vulnerability to hail, and the pattern of destroyed nests was explained well by the interactive effect of maximum estimated size of hail (MESH) and maximum estimated azimuthal wind shear (AWS).